Knock on wood! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The XII World Forestry Congress will be held in Quebec City, Canada from September 21 to 28, 2003, organised by the Canadian Department and the Ministry of Natural Resources, with FAO (the United Nations Food and Agriculture Organization). The...